GAMBARAN PENGETAHUAN SIKAP DAN PERILAKU PERSONALHYGIENE PADA PEMULUNG SAMPAH DI TEMPAT PEMROSESANAKHIR (TPA) WINONG - Barni; Arina Dwi Saputri (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2021)
Garbage is still a problem, therefore one of the efforts of the Banjarnegara Regency Government to overcome the waste problem is to create a Winong Final Processing Site (FPS). The existence of the FPS creates a new job, namely scavengers. The presence of scavengers has a high risk of contracting various diseases such as diarrhea, scabies, and infections. The purpose of this study was to describe the knowledge, attitudes and behavior of scavengers regarding personal hygiene. This study uses a descriptive approach. The research was conducted at the Winong FPS, Banjarnegara Regency with a population of 19 scavengers as respondents. The research sample was taken using incidental sampling technique. Data were obtained from interviews and checklist observations on the knowledge, attitudes, and behavior of garbage scavengers. Data analysis was carried out in a univariate methode. The results showed that the description of knowledge about personal hygiene of respondents was in good category as much as 94.73%, attitudes about personal hygiene of respondents were all good, namely 100%, and personal hygiene behavior of respondents was all positive, namely 100%.